Disseminated Nocardia beijingensis Masquerading as Pulmonary Tuberculosis in a Patient With Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome. (21st May 2020) - Bertrán-López, Jovanna; Abbott, Andrew; Archibald, Lennox K; Benninger, Lauryn; Lascano, Jorge; Kalyatanda, Gautam
Abstract: Case of disseminated Nocardia beijingensis, initially diagnosed and treated by health department as tuberculosis, presented with worsening symptoms and new lesions. Adjustment to antinocardial treatment resulted in significant clinical and radiographic improvement. Maintain a high index of suspicion for Nocardia in patients diagnosed with tuberculosis with worsening lesions despite therapy.